ANALISIS DAMPAK BANJIR DI NAGARI TAROK KECAMATAN LUBUK TAROK KABUPATEN SIJUNJUNG - Deni Agusti; Nefilinda; Rozana Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine and analyze the impact of flooding on the community in Lubuk Tarok Village. Quantitative and qualitative methods were used in this study. A qualitative approach was employed in the study. The method used was a literature review, which reviewed previous findings related to quantitative and qualitative research approaches, as well as the research stages. The population in this study was 2,112 residents of Lubuk Tarok Village. A sample size of 93 residents was selected using random sampling. The results indicate that Lubuk Tarok Village has a very high level of flood vulnerability, with approximately 74.6% of its total area classified as vulnerable and another 25.4% classified as very vulnerable. Further analysis revealed that the main factors contributing to the high flood vulnerability in this area include high rainfall, low-lying topography, poorly absorbent soil, and gentle slopes. The impact of the flood on the community of Nagari Lubuk Tarok was significant and multidimensional, including significant economic losses due to damage to agricultural land and housing, social disruptions such as reduced social interaction and inter-community conflict, and health problems such as skin diseases, diarrhea, and fever. Although flood mitigation efforts have been undertaken by the government and community, such as independent evacuation, mutual cooperation, and the provision of logistical assistance, significant improvements in flood control infrastructure, more effective early warning systems, and sustainability programs are still needed to strengthen community resilience to flood disasters and accelerate post-flood recovery.